2019
DOI: 10.1182/hematology.2019001323
|View full text |Cite
|
Sign up to set email alerts
|

How we perform haploidentical stem cell transplantation with posttransplant cyclophosphamide

Abstract: HLA-haploidentical hematopoietic stem cell transplantation is now one of the most commonly employed alternative donor techniques, with most centers applying T-cell–replete strategies such as that developed by the Baltimore group using high-dose posttransplant cyclophosphamide. HLA-haploidentical hematopoietic stem cell transplantation using posttransplant cyclophosphamide is associated with low rates of severe graft-versus-host disease and nonrelapse mortality and does not require graft manipulation or storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Hematopoietic stem cell transplantation (HSCT) using autologous or allogeneic graft tissue sources is a potentially curative treatment for patients with malignant and nonmalignant blood diseases. However, the clinical value of HSCT remains limited by its high potential for complications, including graft-vs-host-disease (GVHD), delayed immune reconstitution, and graft failure (1,2). Recovery of neutrophil and platelet populations is a key indicator of engraftment success that usually occurs between 14 and 25 days posttransplant, with delays beyond this window increasing the chances of mortality due to infection (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematopoietic stem cell transplantation (HSCT) using autologous or allogeneic graft tissue sources is a potentially curative treatment for patients with malignant and nonmalignant blood diseases. However, the clinical value of HSCT remains limited by its high potential for complications, including graft-vs-host-disease (GVHD), delayed immune reconstitution, and graft failure (1,2). Recovery of neutrophil and platelet populations is a key indicator of engraftment success that usually occurs between 14 and 25 days posttransplant, with delays beyond this window increasing the chances of mortality due to infection (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of neutrophil and platelet populations is a key indicator of engraftment success that usually occurs between 14 and 25 days posttransplant, with delays beyond this window increasing the chances of mortality due to infection (3,4). Furthermore, the late reconstitution of other immune lineages, which can also demonstrate substantial variability, may carry longterm consequences for patient health, including influencing the likelihood of disease relapse (1)(2)(3)(4). Factors that impact the capacity of human hematopoietic stem and progenitor cells (HSPCs) to engraft and differentiate, and the resulting dynamics of human hematopoietic reconstitution remain poorly understood, underscoring the need for new research strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only approximately 25% of siblings are HLA-matched, and usually, the only alternatives are unrelated or haploidentical donors [39]. A recent study has reported that post-transplant cyclophosphamide in HLA-haploidentical HSCT is associated with low rates of severe graft-versus-host disease and its efficacy is comparable with HLA-matched HSCT [40].…”
Section: Discussionmentioning
confidence: 99%
“…Table S5 shows the number of patients with aGvHD for individual studies which report the grade and organs implicated (see Additional file, pp. [38][39][40]. Most of the included patients suffered grade III-IV (82.99%).…”
Section: Mesenchymal Stromal Cells For the Treatment Of Steroidrefracmentioning
confidence: 99%